DEVELOPING LEADERS IN HIGHER EDUCATION: UNIVERSITY FACULTY EXPLORE SELF-MENTORINGâ„¢ - Carr, Marsha L. (European Scientific Journal, ESJ, 2014)
In higher education, where new faculty may lack assurance to lead in the university setting and where it is critical for faculty to learn how to lead successfully in this environment, self-mentoring can provide a means for faculty to build confidence through self-developmentto which all faculty, new and existing, can become leaders in any setting. Faculty in higher education is akin to other systems when it comes to providing a strong program of support for newly hired instructors. Brightman (2005) suggests there are three components for teaching to improve at the college level. The first two factors are a valid and reliable student evaluation instrument accompanied by a norming report for comparative and diagnostic information. The third, and what is believed to be the most significant, is a mentoring process. The purpose of this paper is to review practices of support that are available to new faculty with focus on a study applying self-mentoring, a new program that has recently gained international attention.